Exploring Strategies to Facilitate Student Participation in Speaking Classes - Achekzai, Pohanwal Zarghona (Integrated Journal for Research in Arts and Humanities, 2024)
Speaking is one of the essential skills for learning a language that should be learned through practice and participation. The goal of this research is to find out strategies that facilitate students’ participation in speaking classroom. The participants of the study were 20 students (10) male and 10 females) from junior class of English department of Kabul Education University. It has been found that there are good strategies for increasing student’s participation in speaking classroom. Data showed that 21% of the participants strongly agreed that promoting self-confidence will facilitate their participation in speaking classroom, different percentage of the participants also agreed on stimulating task and present them properly, pleasant and supportive environment, positive way to error correction, employing cooperative work stimulate them to participate in speaking classroom. 5% of the participants agreed that teacher establish a supportive relationship and familiarizing students with English related values increase their participation in speaking classroom. 4% of the participants agreed with Promote group cohesiveness. These facilitating strategies will help instructors to increase their students’ participation in speaking classroom.